Collective Reflective Equilibrium, Algorithmic Bioethics and Complex Ethics - Savulescu, Julian 1963- (2025)
John Harris has made many seminal contributions to bioethics. Two of these are in the ethics of resource allocation. Firstly, he proposed the "fair innings argument" which was the first sufficientarian approach to distributive justice. Resources should be provided to ensure people have a fair innings—when Harris first wrote this, around 70 years of life, but perhaps now 80. Secondly, Harris famously advanced the egalitarian position in response to utilitarian approaches to allocation (such as maximizing Quality Adjusted Life Years [QALYs]) that what people want is the greatest chance of the longest, best quality life for themselves, and justice requires treating these claims equally. Harris thus proposed both sufficientarian and egalitarian approaches. This chapter compares these approaches with utilitarian and contractualist approaches and provides a methodology for deciding among these (Collective Reflective Equilibrium). This methodology is applied to the allocation of ventilators in the pandemic (as an example) and an ethical algorithm for their deployment created. This paper describes the concept of algorithmic bioethics as a way of addressing pluralism of values and context specificity of moral judgment and policy, and addressing complex ethics.
Keywords: Age; Covid-19; John Harris; QALYs; algorithmic bioethics; collective reflective equilibrium; contractualist approaches; fair innings argument; sufficientarian approach; Value pluralism